Friedel-Crafts Alkylation of Indoles with Trichloroacetimidates. - Suzuki, Tamie (Tetrahedron Lett, 2019)
Substituted indole scaffolds are often utilized in medicinal chemistry as they regularly possess significant pharmacological activity. Therefore the development of simple, inexpensive and efficient methods for alkylating the indole heterocycle continues to be an active research area. Reported are reactions of trichloroacetimidate electrophiles and indoles to address the challenges of accessing alkyl decorated indole structures. These alkylations perform best when either the indole or the imidate is functionalized with electron withdrawing groups to avoid polyalkylation.